A STUDY ON ADVERSE DRUG REACTIONS IN HOSPITALIZED PATIENTS WITH DIABETES MELLITUS IN A MULTI -SPECIALITY TEACHING HOSPITAL - Shareef, Javedh; Fernandes, Jennifer; Samaga, Laxminarayana; Khader, Shifaz Abdul (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Adverse drug reactions (ADRs) are well known to occur with any class of drugs when used in normal doses for the management of diseases. Anti-diabetic agents are no exception to this. The main aim of the study was to detect and analyze ADRs in hospitalized patients with diabetes mellitus in a multi-specialty hospital. Methods: The prospective observational study was conducted in a 1000 bed multi-disciplinary teaching hospital at Dakshin Kannada district in south India over a period of 2-year between June 2013 and May 2015. Results: A total of 102 ADRs were reported from 99 patients during the study period with male predominance (60.60%) over females. The average age of the patients in the study was found to be 59.8Â±13.15 years. The majority of the ADRs occurred in the age group of 40-80 years. The average duration of diabetes mellitus in the study was 10.08Â±7.69 years. The class of drugs most commonly responsible for causing ADRs was found to be anti-diabetic drugs (67.64%) followed by antimicrobial agents (10.78%). The most commonly occurred ADRs was hypoglycemia (63.72%) followed by gastritis (6.86%). Causality assessment by using Naranjo scale indicated that majority of the ADRs (59.80%) were probable, 37.25% were possible, and 2.94% were definite. The severity assessment using the Hartwig and Siegal scale indicated that the majority of the ADRs were mildâ€ followed by moderateâ€ and severe,â€ respectively. Preventability assessment using modified Schumock and Thornton revealed that 57.84% were definitely preventable, 33.33% were probably preventable, and 8.82% were not preventable. Conclusion: The study shows that the active involvement of a clinical pharmacist helps in monitoring and detecting ARDs and their management through therapeutic interventions would be beneficial in the better patient outcome. Keywords: Adverse drug reaction, Diabetes mellitus, Clinical pharmacist.